Beyond glycemia: clinical nutrition in type 2 diabetes and cardiometabolic risk - Antonio Maria Labate; Provvidenza Villari (Academia Nutrition and Dietetics, 2026)
Type 2 diabetes (T2D) is a multifactorial cardiometabolic disorder in which dysglycemia coexists with visceral adiposity, insulin resistance, atherogenic dyslipidemia, hypertension, and metabolic dysfunction-associated steatotic liver disease (MASLD). In this setting, clinical nutrition should be considered a therapeutic intervention rather than a generic lifestyle add-on. This mini-review summarizes how nutritional strategies can modify major cardiometabolic domains in adults with T2D, with a practical focus on Mediterranean-style dietary patterns, weight-oriented interventions, lower-carbohydrate approaches, and the challenges of implementation in routine care. Current evidence supports Mediterranean-style eating patterns as a broadly applicable benchmark because of their favorable effects on glycemic control, lipid profile, blood pressure, and cardiovascular risk. Weight-loss-oriented nutritional care remains central in people with overweight or obesity, particularly when reductions in visceral adiposity and liver fat are desirable. Lower-carbohydrate approaches may offer benefits in selected patients, especially for postprandial glycemia and hypertriglyceridemia, whereas ketogenic diets require greater caution because of sustainability, dietary quality, and safety concerns in specific pharmacological contexts. Overall, the literature supports a personalized, quality-focused, and sustainable nutritional approach. The greatest clinical value of nutrition in T2D lies not only in lowering glycated hemoglobin (HbA1c), but also in addressing the broader metabolic determinants that drive long-term cardiovascular and hepatic risk.